Chatter : Dispatches from the Secret World of Global Eavesdropping - Keefe, Patrick Radden 1976- (New York Random House, 2005)
A look inside the secret world of the American intelligence establishment and its link to the global eavesdropping network "Echelon" assesses how much privacy Americans have unwittingly sacrificed in favor of national security.
Include Glossary and Index
Keywords: Intelligence service -- United States. -- Eavesdropping -- United States. -- Wiretapping -- United States